Localized-magnon states in strongly frustrated quantum spin lattices - Richter, J. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2005)
Recent developments concerning localized-magnon eigenstates in strongly frustrated spin latticesand their effect on the low-temperature physics of these systems in high magnetic fields arereviewed. After illustrating the construction and the properties of localized-magnon states we describethe plateau and the jump in the magnetization process caused by these states. Considering appropriate lattice deformations fitting to the localized magnons we discuss a spin-Peierls instability in high magnetic fields related to these states. Last but not least we consider the degeneracy of the localized-magnon eigenstates and the related thermodynamics in high magnetic fields. In particular, we discuss the low-temperature maximum in the isothermal entropy versus field curve and the resulting enhanced magnetocaloric effect, which allows efficient magnetic cooling from quitelarge temperatures down to very low ones.